Generic options: Variable use of vos and uno in Patagonia Spanish (Argentina) - Zanfardini, Lucia (2023)
The distribution of vos ‘you’ and uno ‘one’ in generic messages is studied in a corpus of female speakers of Spanish (Argentina).The question was how it is possible that the form vos, so clearly defined as the pronoun to refer to the interlocutor, could have an impersonal reading, alongside the indefinite pronoun uno, which seems much more fit to do the job. The alternation between the generic use of the forms vos and uno cannot be, in our view, the result of chance nor a merely stylistic tool, but corresponds to the communicative strategies that speakers utilize in each and every context. This paper studies the different factors that play a role in the selection of each of the pronouns.